Evaluation of Feeder Transport Integration Policy in the Bus Rapid Transit System in Jakarta for Non-BRT Transjakarta Services - Agustiar, Vaninta Priskila; Sururi, Ahmad (Indonesian Journal of Social Science Research, 2025)
The DKI Jakarta Provincial Government has implemented a policy of integrating feeder transportation into the Bus Rapid Transit (BRT) system to improve the efficiency, speed, safety, and affordability of public transportation services. This study uses a descriptive qualitative method with a policy evaluation approach based on six criteria from William N. Dunn: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. Data were collected through observation, interviews, and documentation, then analyzed through the process of reduction, presentation, and drawing conclusions. The results of the study indicate that in terms of effectiveness, the integration of NonBRT services has increased the accessibility and connectivity of public transportation, as seen from the increasing number of users after the pandemic. However, in terms of efficiency, travel time is still influenced by dynamic traffic conditions due to mixed traffic, although human resource and budget management have been running well. The adequacy criteria indicate that the service has covered most of the community's needs, including the suburbs. In terms of equality, the benefits of the policy have been felt fairly, but supporting infrastructure is not evenly distributed throughout Jakarta. The responsiveness of policy implementers is quite good, with the existence of complaint channels and quick responses to public complaints. Finally, in terms of accuracy, this policy has answered the need for mobility in densely populated areas and areas not yet served by the main BRT route.